Foster rather than biological parental telomere length predicts offspring survival and telomere length in king penguins. Issue 16 (20th June 2020) - Viblanc, Vincent A.; Schull, Quentin; Stier, Antoine; Durand, Laureline; Lefol, Emilie; Robin, Jean‐Patrice; Zahn, Sandrine; Bize, Pierre; Criscuolo, François
Abstract: Because telomere length and dynamics relate to individual growth, reproductive investment and survival, telomeres have emerged as possible markers of individual quality. Here, we tested the hypothesis that, in species with parental care, parental telomere length can be a marker of parental quality that predicts offspring phenotype and survival. In king penguins ( Aptenodytes patagonicus ), we experimentally swapped the single egg of 66 breeding pairs just after egg laying to disentangle the contribution of prelaying parental quality (e.g., genetics, investment in the egg) and/or postlaying parental quality (e.g., incubation, postnatal feeding rate) on offspring growth, telomere length and survival. Parental quality was estimated through the joint effects of biological and foster parent telomere length on offspring traits, both soon after hatching (day 10) and at the end of the prewinter growth period (day 105). We expected that offspring traits would be mostly related to the telomere lengths (i.e., quality) of biological parents at day 10 and to the telomere lengths of foster parents at day 105. Results show that chick survival up to 10 days was negatively related to biological fathers' telomere length, whereas survival up to 105 days was positively related to foster fathers' telomere lengths. Chick growth was not related to either biological or foster parents' telomere length. Chick telomere length was positively related to foster mothers' telomere length at both 10 and 105 days. Overall, our study shows that, in a species with biparental care, parents' telomere length is foremost a proxy of postlaying parental care quality, supporting the "telomere – parental quality hypothesis."